How I treat anal squamous cell carcinoma. (3rd September 2020) - Martini, Giulia; Arrichiello, Gianluca; Borrelli, Carola; Poliero, Luca; Martinelli, Erika
Abstract : Squamous cell carcinoma of the anus (SCCA) is a rising health issue, strongly related to other relevant medical conditions such as (HIV) and human papillomavirus (HPV) infection. Correct assessment of patients with SCCA requires a multidisciplinary evaluation and adequate follow-up. Accurate local and systemic staging, as well as risk evaluation, are essential to optimal treatment planning. Early stage tumours can be definitively treated with a combination of chemotherapy and radiotherapy, while salvage surgery is usually reserved for patients who develop local recurrence. Distant recurrence and de novo metastatic disease are associated with poorer prognosis and require palliative systemic chemotherapy, with different single agent and combination options available. Finally, recent discoveries on the carcinogenesis of SCCA have allowed the development of innovative treatment options, the most promising being immune checkpoint inhibitors. The limited systemic treatments for SCCA and low incidence of the disease, together with insufficient data from clinical research could explain the poor outcomes of these patients, which should therefore be managed in high volume centres and enrolled in clinical trials whenever possible. This article summarises the main strategies for treating patients with SCCA.